THE INFLUENCE OF THE 5E LEARNING CYCLE MODEL USING GELKON PUZZLE MEDIA ON THE LEARNING OUTCOMES OF GRADE XI STUDENTS AT SMA NEGERI 09 BENGKULU CITY - Yusdiarti, Mezi; Hidayat, Tomi (Universitas PGRI Sumatera Barat, 2024)
This study aims to determine the influence of the 5E Learning Cycle model using GELKON (concept glass) puzzles as a learning medium on the academic performance of Grade XI science students at SMAN 9 Bengkulu City. An experimental method was used, with the sample population including Grade XI Science 1 and Grade XI Science 2 classes. Data analysis techniques involved normality tests, homogeneity tests, and hypothesis testing using a post-test t-test for final ability measurement. The study concludes that the Learning Cycle model positively impacts student learning outcomes in Grade XI science classes at SMA Negeri 09 Bengkulu City. The Learning Cycle model using GELKON puzzles as a medium showed a greater improvement in student learning outcomes compared to conventional methods. This was evidenced by the increase in the average post-test score: Grade XI Science 1 (conventional method) had an average score of 79.48, while Grade XI Science 2 (Learning Cycle method) had an average score of 90.00.